Correction to: Impact of comorbid subthreshold depressive symptoms on cancer-related fatigue and complications in adults with leukemia - Yue-Xian Liu; Juan Wang (World Journal of Psychiatry, 2025)
Correction to "Liu YX, Wang J. Impact of comorbid subthreshold depressive symptoms on cancer-related fatigue and complications in adults with leukemia. World J Psychiatry 2024; 14(7): 1009-1016 [PMID: 39050202 DOI: 10.5498/wjp.v14.i7.1009]". In the methods section of this article's abstract needs to be corrected.